Forest Management in the Interface: Reducing Fire Risk - Bruce Hull; Sarah F. Ashton; Rien M. Visser; Martha C. Monroe (EDIS)
Wildfire is one of the most serious and publicized challenges facing interface forest management. Wildfires can change forest vegetation, affect human health, and cause millions of dollars’ worth of damage to homes, businesses, timber, and tourism. This revised 5-page fact sheet outlines tips for the firewise community development, design of structures, landscaping, and fuel reduction. Written by Bruce Hull, Sarah F. Ashton, Rien M. Visser, and Martha C. Monroe, and published by the UF Department of School of Forest Resources and Conservation, August 2012.